Immunogenicity and safety of the booster BNT162b2 vaccine in patients with axial spondyloarthritis treated with biological disease-modifying drugs - Smetanova, Jitka; Milota, Tomas; Rataj, Michal; Hurnakova, Jana; Zelena, Hana; Sediva, Anna; Horvath, Rudolf (Frontiers in Immunology, 2022)
Background: Vaccination confers relatively short-term protection against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), indicating the need for booster doses. Immunocompromised individuals, including those with immune-mediated inflammatory diseases (IMIDs), may have pronounced immune response waning. Vaccine-boosted humoral and T-cell responses minimize poor coronavirus disease 19 (COVID-19) outcome without increasing adverse events (AE). There is limited evidence of third-dose vaccination in axial spondyloarthritis (AxSpA) patients. We investigated immune-response persistence after primary vaccination and immunogenicity and safety after the BNT162b2 booster vaccination. Methods: This prospective observational study enrolled an AxSpA cohort treated with interleukin-17 (IL-17) and tumor necrosis factor-alpha (TNFα) inhibitors. Serum SARS-CoV-2-specific and virus-neutralizing antibodies for humoral response and flow cytometric detection of intracellular cytokines following SARS-CoV-2-specific peptide-based stimulation for T-cell immune responses were assessed, and safety was evaluated via a clinical questionnaire. Results: Fifteen male AxSpA patients treated with TNFα (73·3%) or IL-17 (26·7%) inhibitors were enrolled and had humoral response persistence at 6 months: 905·6 (±186·1 SD) and 409·1 (±335·7) U/mL. Specific antibody concentrations further increased after booster vaccination to 989·7 (±12·62) and 1000 U/mL and T-cell responders from 53·3% to 80%, with no differences between AxSpA (including “vaccination only” and “hybrid immunity” subgroups) and healthy control (HC) cohorts. No severe AE occurred; the AE spectrum was comparable to that of the general population. Conclusion: Immune-response persistence after primary vaccination and immunogenicity after booster vaccination were unaffected by anti-IL17 or anti-TNFα therapy with similar AE as in the general population.